Peeking beyond the wall: analysing university technology transfer and commercialisation processes - Lopes, J.; Farinha, L.; Ferreira, J.; Ferreira, F. (International Journal of Technology Management, 2018)
This paper sought to analyse the dynamics underlying university technology transfer and commercialisation mechanisms. We adopt a qualitative research methodology, which incorporates different case studies, interviews and applied research of the actors involved in universities, business incubators and start-ups. While limited to three case studies, this paper does highlight the technology transfer mechanisms and the support provided to commercialisation, including the identification of the difficulties and opportunities present within the context of cooperation networks. By surveying those running incubators and incubator company managers in conjunction withanalysis of research, development and innovation (RDI) cooperative projects backed by European funding, we were able to gain insights into the different processes of transferring and commercialising technology. Falling within the framework of the third component of universities’ mission, this article demonstrates not only the importance of RDI cooperation networks but also how the consequent commercialisation of new products and services generates positive consequences for economic growth.